2017
DOI: 10.26663/cts.2017.0019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fibrin sealant spraying on prolonged air leak after pulmonary resections: a single center experience

Abstract: 1 81To cite this article: Kumbasar U, Yılmaz Y, Özercan MM, Ancın B, Dikmen E, Doğan R. The effect of fibrin sealant spraying on prolonged air leak after pulmonary resections: a single center experience. Curr Thorac Surg 2017;2(3): 81-84. ABSTRACT Background:The aim of this study is to evaluate the effects of fibrin sealant spraying on postoperative air

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The study of Kumbasar et al [23] revealed postoperative air leak 10.5% in patients with fibrin glue application to 18.2%in patients without glue [p= 0.668] and removal of chest tube range from 2-6 days to 2-14 days in patients using glue versus without glue with p value [0.05].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Kumbasar et al [23] revealed postoperative air leak 10.5% in patients with fibrin glue application to 18.2%in patients without glue [p= 0.668] and removal of chest tube range from 2-6 days to 2-14 days in patients using glue versus without glue with p value [0.05].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be pressureresistant and not allow air leak. 11,12 Federico et al reported that Coseal reduced the rate of air leaks and duration of hospital stay. The material was easy-to-use and caused no morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…19 Based on positive results obtained in emphysema surgery, supporting the stapler line with synthetic or biological materials has been proposed. 12,20 Likewise, the present study investigated the efficacy of Peristrips made of bovine pericardium and Coseal used to support the stapler line on air leak and complications in emphysema patients. In Group 1, where Peristrips alone was used, times to discharge and tube removal were better compared to Group 2, where no Peristrips was used.…”
Section: Discussionmentioning
confidence: 99%